2002
DOI: 10.1073/pnas.222561499
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of serum response factor activity by a family of myocardin-related transcription factors

Abstract: Myocardin is a SAP (SAF-A͞B, Acinus, PIAS) domain transcription factor that associates with serum response factor (SRF) to potently enhance SRF-dependent transcription. Here we describe two myocardin-related transcription factors (MRTFs), A and B, that also interact with SRF and stimulate its transcriptional activity. Whereas myocardin is expressed specifically in cardiac and smooth muscle cells, MRTF-A and -B are expressed in numerous embryonic and adult tissues. In SRF-deficient embryonic stem cells, myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
483
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 438 publications
(501 citation statements)
references
References 31 publications
14
483
0
Order By: Relevance
“…Here we report the cloning of a third member of the myocardin/MKL family, MKL2, in humans. A mouse homologue of this gene, MRTF-B, was also recently identified and a fragment of the gene was previously identified as MAL16 (33,36). We find that MKL2 is broadly expressed, with strong expression in skeletal muscle, and can interact with SRF and activate many CArG box-containing promoters.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Here we report the cloning of a third member of the myocardin/MKL family, MKL2, in humans. A mouse homologue of this gene, MRTF-B, was also recently identified and a fragment of the gene was previously identified as MAL16 (33,36). We find that MKL2 is broadly expressed, with strong expression in skeletal muscle, and can interact with SRF and activate many CArG box-containing promoters.…”
mentioning
confidence: 53%
“…MKL2 Is a Strong Transactivator of CArG Box-dependent Promoters-Because MKL1 and myocardin strongly activate CArG box containing promoters (15,35,36), we checked whether overexpression of MKL2 could also activate CArG box-dependent reporter genes and act as a transcriptional coactivator of SRF. To test this we co-expressed MKL1, MKL2, or an N-terminal deletion of MKL2 (MKL2⌬N) that lacks 71 aa such that it starts at the beginning of the MKL homology domain similar to MKL1 (Fig.…”
Section: Identification and Expression Of Human Mkl2-wementioning
confidence: 99%
“…These findings further support results of the present studies indicating that myocardin alone is insufficient to initiate the entire SMC differentiation program. Of interest, Wang et al 29 showed that expression of the myocardin-related factors, MRTF-A/MAL/MKL1/BSAC and MRTF-B/MKL2, preceded the expression of myocardin, and they were expressed throughout the embryo at E10.5. In addition, they showed that MRTF-A/MAL/MKL1/BSAC potently activated SM22␣ transcription, even in the absence of myocardin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that MRTF-A/MAL/MKL1/BSAC potently activated SM22␣ transcription, even in the absence of myocardin. 29 It is thus possible that these myocardin-related factors may also contribute to initial expression of early SMC markers.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardin-related transcription factors (MRTFs) have been shown to activate serum response factor (SRF) [9][10][11] upon dissociation from G-actin 12 , providing muscle growth and regeneration 13,14 . SRF is co-activated by myocardin 15 or MRTFs A and B 16 .…”
mentioning
confidence: 99%